Manifestasies van Marxisme in die Suid-Afrikaanse samelewingsverband - Oosthuizen, J. S. (Koers, 1985)
The question is often asked why Marxism is so credible still for people of the Third World. The author maintains that this is often so because Marx's description of the position of the worker in a capitalist society has consistently appealed to workers in developed industrial countries, and has helped them to define their position within society for themselves. He goes to explain how Marx's definition of the worker's position in nineteenth century England can be made applicable to the position of the worker in most Third World countries - and in particular also to the position of the Non-White worker in South Africa . He points out a few of the most striking similarities, and comes to the conclusion that there is no doubt that most Non-Whites in South Africa find a socialist/communist dispensation more appealing than a capitalist one. The only way that he can see to change the definition that the Non-White has of changing his definition of his sociopolitical situation is to change South African society. He then outlines certain changes which should enjoy a very high priority in South Africa .